Kajian Kuat Lentur Balok Beton Komposit Dengan Angkur Baja Tulangan - Johanna Indah Mannuela; Novita Cahyaningtyas (Universitas Katolik Soegijapranata Semarang, 2018)
Concrete is a structural element in a building that is widely known and utilized. However, in the construction world there are various problems that occur, one of the problems is on concrete beams. Well planned and designed construction always changes, failures and damage. One way of strengthening and improving the structure is with the method of composting the old concrete beams with new concrete blocks with reinforced steel anchors reinforced with chemicalanchor. This research uses a cylindrical test specimen, normal concrete beam measuring 15 cm × 15 cm × 60 cm, monolith concrete beam measuring 15 cm × 30 cm × 60 cm, and composite concrete beam with reinforced steel anchors reinforced with chemicalanchor HILTI HIT RE-500 V3 is 15 cm × 30 cm × 60 cm. The test was carried out to determine the bending strength values of the normal beam and composite beams and to know the increase of the bending strength values between normal, monolithic and composite concrete beams. The size of the maximum bending moments of concrete beams length 15 cm × 15 cm × 60 cm the biggest is 4820 kg. For the maximum bending moments of the new concrete beam specimens measuring 15 cm × 15 cm × 60 cm is 4110 kg. The average value of long bending strength of old concrete beams measuring 15 cm × 15 cm × 60 cm is 53.06 kg/cm2. For the average value of new flexible concrete beams measuring 15 cm × 15 cm × 60 cm is 51.91 kg/cm2. The maximum bending moments of monolith concrete beam specimens measuring 15 cm × 30 cm × 60 cm is 14733.33 kg. The average flexural strength is 49.11 kg/cm2. The maximum bending moments of composite concrete beam is 15 cm × 30 cm × 60 cm the largest is 13100 kg. For the average bending strength value is 43.67 kg/cm2.